Social protection of young families as a factor of trust in the state: sociological view - K. A. Aramyan; V. V. Krivopuskov; D. R. Kaberova (Цифровая социология)
The institution of the family is the foundation of modern Russian society, a prerequisite for stability and well-being of the state. The article analyses the impact of state social policy on institutional trust of young family Russians on the basis of sociological research data in an innovative way. These results of the survey have showed that the formation of confidence of youth in the state and social well-being of young families need more significant systemic and comprehensive government support measures. The authors reasonably conclude that it is necessary to revise the principle of direct dependence “state support – trust of youth” in relation to this social category, since young married couples have their own particular matrix of values and relationships in the “I – family – state” triad. These factors dictate the need to adjust the package of social protection (support) measures for families with consideration to their real requests: strengthening the economic component (reduction of bureaucratic barriers, tax burden, support for small and medium-sized enterprises and firms that are led, as a rule, by representatives of young married couples); organising a network of centres for specialised psychological assistance to pregnant women and their husbands, then psychological and pedagogical accompaniment of parents; targeting information state policy (with an emphasis on the parental channel), as well as through programmes of educational shifts of youth camps (formation of knowledge among young generations of Russians even before marriage about the state policy of family protection (support), social trust and confidence in their well-being in the future). At the same time, the results of the study emphasise the need for a constant sociological analysis of the effectiveness of the public policy and social protection (support) as a measure of managerial influence on youth and young families – a mobile and ever-changing stratum of civil society.